The dual role of CD6 as a therapeutic target in cancer and autoimmune disease - Gurrea-Rubio, Mikel; Fox, David A. (Frontiers in Medicine, 2022)
Autoimmune disease involves loss of tolerance to self-antigen, while progression of cancer reflects insufficient recognition and response of the immune system to malignant cells. With the introduction of immunotherapy as a treatment for cancer, there is increased focus on the biological pathways that link cancer and its treatment with autoimmunity. In this review, we hope to consolidate our understanding of current and emerging molecular targets to treat cancer and autoimmunity simultaneously, with a special focus on CD6.